Sledenje onesnaženja s cinkom v ekosistemu vinograda - Bukovac, Vesna; Muršec, Mateja (University of Maribor Press, 2017)
Follow-up of Zinc Pollution in the Vineyard Ecosystem. In the monograph, the problem of tracing heavy metal - a zinc, which is introduced in the ecosystem of the vineyard through the use of organometallic plant protection products - is presented in a sufficient and necessary way. Zinc is an integral part of the active component of Antracol, which is widely used in viticulture as a contact fungicide. The study confirms that the increased zinc content in vineyard soil is mainly due to the long-term use of organometallic plant protection products. By focusing on the problem of soil in the vineyard, the sensitivity of the balance in the anthropogenic modified ecosystem, the zinc chemistry in the soil, and, last but not least, the guidelines for the restoration of contaminated soils, the monograph contains a comprehensive perspective on the topic under consideration. The results of the research are compared with the findings of researchers in the world, therefore the presented knowledge is very topical. Knowing about the natural circulation of the substances introduced into the soil and transferring them into the food chain, the content of the monograph aims to address the reputed auditorium on the importance of tracking pollution in the environment and the urgent need for immediate action.